The Mla system and its role in maintaining outer membrane barrier function in Stenotrophomonas maltophilia - Coves, Xavier; Mamat, Uwe; Conchillo-Solé, Oscar; Huedo, Pol; Bravo, Marc; Gómez, Andromeda-Celeste; Krohn, Ines; Streit, Wolfgang R.; Schaible, Ulrich E.; Gibert, Isidre; Daura, Xavier; Yero, Daniel (Frontiers in Cellular and Infection Microbiology, 2024)
Stenotrophomonas maltophilia are ubiquitous Gram-negative bacteria found in both natural and clinical environments. It is a remarkably adaptable species capable of thriving in various environments, thanks to the plasticity of its genome and a diverse array of genes that encode a wide range of functions. Among these functions, one notable trait is its remarkable ability to resist various antimicrobial agents, primarily through mechanisms that regulate the diffusion across cell membranes. We have investigated the Mla ABC transport system of S. maltophilia, which in other Gram-negative bacteria is known to transport phospholipids across the periplasm and is involved in maintaining outer membrane homeostasis. First, we structurally and functionally characterized the periplasmic substratebinding protein MlaC, which determines the specificity of this system. The predicted structure of the S. maltophilia MlaC protein revealed a hydrophobic cavity of sufficient size to accommodate the phospholipids commonly found in this species. Moreover, recombinant MlaC produced heterologously demonstrated the ability to bind phospholipids.Gene knockout experiments in S. maltophilia K279a revealed that the Mla system is involved in baseline resistance to antimicrobial and antibiofilm agents, especially those with divalent-cation chelating activity. Co-culture experiments with Pseudomonas aeruginosa also showed a significant contribution of this system to the cooperation between both species in the formation of polymicrobial biofilms. As suggested for other Gram-negative pathogenic microorganisms, this system emerges as an appealing target for potential combined antimicrobial therapies.